Prepectoral Breast Reconstruction Reduces Opioid Consumption and Pain After Mastectomy: A Head-to-Head Comparison With Submuscular Reconstruction. Issue 5 (9th November 2022) - Holland, Michael; Su, Paul; Piper, Merisa; Withers, Jacquelyn; Harbell, Monica W.; Bokoch, Michael P.; Sbitany, Hani
Abstract : Background: Acute pain after mastectomy is increased with concurrent breast reconstruction. One postulated advantage of prepectoral breast reconstruction is less postoperative pain; however, no comparisons to partial submuscular reconstruction have been made to date. Here, we examined the postoperative pain experienced between patients with prepectoral and subpectoral breast reconstruction after mastectomy. Methods: We performed a retrospective chart review of all patients undergoing immediate breast reconstruction with tissue expanders from 2012 to 2019 by a single plastic surgeon. Patient demographics, surgical details, and anesthetic techniques were evaluated, and our primary outcome compared postoperative opioid usage between prepectoral and subpectoral reconstructions. Our secondary outcome compared pain scores between techniques. Results: A total of 211 subpectoral and 117 prepectoral reconstruction patients were included for analysis. Patients with subpectoral reconstructions had higher postoperative opioid usage (80.0 vs 45.0 oral morphine equivalents, P < 0.001). Subpectoral patients also recorded higher maximum pain scores compared with prepectoral reconstructions while admitted (7 of 10 vs 5 of 10, P < 0.004). Multivariable linear regression suggests that mastectomy type and subpectoral reconstruction were significant contributors to postoperative opioid use ( P < 0.05). Conclusions: Prepectoral breast reconstruction was associated with less postoperative opioid consumption and lower postoperative pain scores as compared with subpectoral reconstruction, when controlling for other surgical and anesthesia factors. Future randomized controlled trials are warranted to study how postoperative pain and chronic pain are influenced by the location of prosthesis placement in implant-based postmastectomy breast reconstruction.